FAKTOR-FAKTOR PENYEBAB STRES PADA MAHASISWA KEPERAWATAN YANG PERTAMA KALI MENJALANI PRAKTIK KLINIK - Sri Devi Eflia Putri; Veny Elita; Ganis Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Clinical practice is one of academic programs in nursing faculty which is held in the first year. This program often leads the first year students get stressed. This research aims to identified the factors that could caused stress for the nursing students during their first clinical practice. This research was conducted at the Faculty Nursing of Riau University on July 2018 by using descriptive method with correlative analysis and cross sectional approach. There are 150 respondents taken by considering the inclusion criteria using accident sampling technic. The measuring instrument is Depression Anxiety Stres Scales (DASS) questionnaire to find the variable of stress level and Perceived Stress Scale (PSS) questionnaire to find the variable of stress factors. The analysis that is applied is univariate analysis as it aims to seeks the frequency distribution and bivariate by using chi-square test. In addition, the factors relating to the stress level for the students are assignment and workload (p = 0,009), relation with co-workers (p = 0,006), knowledge (p = 0,008), skill in treating the patients (p = 0,002) and lecturers’ support (p = 0,004). The factors unrelated to the stress level for the students is environment (p = 0,508). The result of the research is the most of nursing students have moderate level of stress like feeling tired, tired easily, and can’t relax. It is suggested to the nursing students to prepare themselves before implementing clinical practice to prevent the stress and beneficial to the nursing care provide. Keyword : DSS, first clinical practice, nursing students, PSS, stress level.